Synthesis and characterization of heterocyclic dyes containing a thienyl bridge for dye sensitized solar cells - Fernandes, Sara S. M. (2014)
The ever increasing consumption of fossil fuels, causing global warming and environmental pollution, has led to a greater focus on renewable energy sources and sustainable development. Among several new energy technologies, solar cells utilizing the sun as an energy source are the most promising [1]. Solar cells based on dye sensitizers (DSSCs) adsorbed on nanocrystalline TiO2 electrodes have received significant attention because of their high incident solar light-to-electricity conversion efficiency, the structural diversity of organic molecules that allows accurate adjustment of the photophysical properties, colourful and decorative natures and low cost of production. As a result, in the last two decades, a wide range of structural modifications to the donor and/or acceptor group and pi-bridge have been carried out having in mind the preparation of organic chromophores with high performance for DSSCs [1]. In this communication we report on the synthesis of a novel heterocyclic dye and its characterization as a sensitizer for dye-sensitized solar cells.